This luminous coast : walking England's eastern edge - Pretty, Jules N. (Comstock Publishing Associates, a division of Cornell University Press, 2014)
Over the course of a year, Jules Pretty walked along the shoreline of East Anglia in southeastern England, eventually exploring four hundred miles on foot (and another hundred miles by boat). It is a coast and a culture that is about to be lost--not yet, perhaps, but soon--to rising tides and industrial sprawl. This Luminous Coast takes the reader with him on his journey over land and water; over sea walls of dried grass, beside stretched fields of golden crops, alongside white sails gliding across the intricate lacework of invisible creeks and estuaries, under vast skies that are home to curlews and redshanks and the outpourings of skylarks. East Anglia's coastline is as much a human landscape as it is a natural one, and Pretty is equally perceptive about the region's cultural heritage and its "industrial wild": fishing villages and the modern seaside resorts, family farms and oil refineries, pleasure piers and concrete seawalls, cozy pubs and military installations. Through words and photographs, Pretty interweaves stories of the land and sea with people past and present. He is a passionate and sensitive guide to a region in transition, under stress, and perhaps even doomed, as finely attuned to its history as he is to its unique sensory world